2019
DOI: 10.1021/acs.inorgchem.9b01981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Gold Porphyrin Linked to Malonate Diamine Platinum Complexes

Abstract: Recently, Gold(III) porphyrins have gained great interest as anticancer drugs not only for stability of gold(III), but also for the functionalization of porphyrin to allow bridging with another metal such as platinum(II). We report here, for the first time, the synthesis of three new bi-metal compounds containing gold(III) porphyrin conjugated to a platinum diamine moiety through malonate bridging to obtain enhanced cytotoxicity from both metals combined to the phototoxicity of the porphyrin. The three complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Organic dyes such as porphyrins, chlorins, phthalocyanines, and xanthenes are often used in PDT [ 87 , 88 ]. However, this class of compounds is prone to photobleaching, have low light-dark cytotoxicity ratios, and is also known to form aggregates that decrease the singlet oxygen generation efficiency as a function of the elapsed time, and thus decreases the efficiency of the treatment [ 89 ]. Additionally, the need for continuous in situ illumination causes damage to the skin and tissues.…”
Section: Persistent Luminescence In Luminescence Imaging Of Biologmentioning
confidence: 99%
“…Organic dyes such as porphyrins, chlorins, phthalocyanines, and xanthenes are often used in PDT [ 87 , 88 ]. However, this class of compounds is prone to photobleaching, have low light-dark cytotoxicity ratios, and is also known to form aggregates that decrease the singlet oxygen generation efficiency as a function of the elapsed time, and thus decreases the efficiency of the treatment [ 89 ]. Additionally, the need for continuous in situ illumination causes damage to the skin and tissues.…”
Section: Persistent Luminescence In Luminescence Imaging Of Biologmentioning
confidence: 99%
“…The porphyrin ligand can stabilize the gold(III) ion against demetalation and reduction by the biological reductant glutathione (Sun et al, 2010 ). In vitro biological studies have proven the high anticancer potency of gold(III) porphyrin complexes against a wide range of cancer cell lines, such as neuroblastoma, melanoma, ovarian, breast, colorectal, lung, and nasopharyngeal cancers, with IC 50 values at low micromolar or even nanomolar levels (Lammer et al, 2015 ; Toubia et al, 2019 ). Moreover, in vivo studies have demonstrated the promising tumor growth inhibitory ability of gold(III) porphyrins in different mouse models of cancer ( Figures 2A,B,D ) and the induction of apoptosis in tumor xenograft tissues ( Figure 2E ).…”
Section: Anticancer Gold(iii) Porphyrin Complexesmentioning
confidence: 99%
“…Therefore, chalcone has potential research value in the field of new pesticide synthesis. Malonate compounds are important raw materials for the synthesis of many pharmaceutical intermediates and their pharmacologically effective groups also have antibacterial, antiviral, anticancer, anti‐inflammatory and other biological activities.…”
Section: Introductionmentioning
confidence: 99%